Corruption as the Bane of Nigeria’s Security - Mohammed, Mohammed Ibrahim; Adamu, Sunusi; Pius, Oki Olaniyi (Kashere Journal of Politics and International Relations, 2023)
Corruption has been one of the pandemics that put the security and peace of Nigerians in jeopardy. From the country's independence in October, 1960 to date, hundreds of trillions were estimated to have been siphoned by stakeholders in various key positions in the country, thereby leading to harsh socio-economic realities that have direct negative impacts on the security of lives and properties of people in the country. Thus, this paper is specifically set to discuss how corruption leads to security challenges in Nigeria. The paper reviewed the literature thematically, and used frustration-aggression theory as its theoretical framework. Also, the data for the research was completely generated from secondary sources, through textbooks, journals, periodicals and newspapers, and the content analysis method was adopted in the analysis of the data gathered. Based on that, the research arrived at the findings that corruption is the major element that created the security challenges face in Southern and Northern Nigerian states. Likewise, the research discovered that corruption in the security sector aggravated the situation and made Nigerian security agencies incapable of executing the fight against insecurity in all the sections of the country. Finally, the research recommends the need to strengthen the activities of various anti-graft agencies in the country in such a manner that they will work without bias or favour, and at the same time, hard punishments like that of China, Morocco etc. need to be enforced against anyone found guilty of corrupt practice in the country.